Intra-Articular Injection of Fructus Ligustri Lucidi Extract Attenuates Pain Behavior and Cartilage Degeneration in Mono-Iodoacetate Induced Osteoarthritic Rats - Yan, Bo; Zhou, Li; Wang, Caiwei; Wang, Rongrong; Yan, Li; Yu, Lingying; Liu, Fucun; Du, Wenxi; Yu, Guangping; Yuan, Qiang; Tong, Peijian; Shan, Letian; et al. (Frontiers in Pharmacology, 2018)
Fructus Ligustri Lucidi (FLL) has been widely used as a traditional Chinese medicine (TCM) for treating soreness and weakness of waist and knees. It has potential for treating OA owing to its kidney-tonifying activity with bone-strengthening effects, but there is so far no report of its anti-OA effect. This study established a rat OA model by intra-articular (IA) injection of mono-iodoacetate (1.5 mg) and weekly treated by IA administration of FLL at 100 μg/mL for four weeks. Thermal withdrawal latency, mechanical withdrawal threshold, and spontaneous activity were tested for evaluation of pain behavior, and histopathological (HE, SO, and ABH staining) and immunohistochemical (Col2, Col10, and MMP13) analyses were conducted for observation of cartilage degradation. In vitro effect of FLL on chondrocytes was evaluated by MTT assay and qPCR analysis. Moreover, HPLC analysis was performed to determine its chemoprofile. The pain behavioral data showed that FLL attenuated joint pain hypersensitivity by increasing thresholds of mechanical allodynia and thermal hyperalgesia as well as spontaneous activity. The histopathological result showed that FLL reversed OA cartilage degradation by protecting chondrocytes and extracellular matrix in cartilage, and the immunohistochemical analysis revealed its molecular actions on protein expressions of MMP13, Col2, and Col10 in cartilage. The MTT assay showed its proliferative effects on chondrocytes, and qPCR assay clarified its mechanism associated with gene expressions of Mmp13, Col2, Col10, Adamts5, Aggrecan, and Runx2 in TNF-α treated chondrocytes. Our results revealed an anti-OA effect of FLL on pain behavior and cartilage degradation in OA rats and clarified a molecular mechanism in association with the suppression of chondrocyte hypertrophy and catabolism. IA FLL can be regarded as novel and promising option for OA therapy.